111 The Degree and Time Course of Platelet Inhibition Following the Administration of Oral Antiplatelet Agents in Patients Presenting with ST Elevation MI (STEMI). (3rd June 2016) - Khan, Nazish; Vincent, Amoah; Smallwood, Andrew; Wrigley, Ben; Martins, Joe; Khogali, Saib; Shahzad, Munir; Alan, Nevill; Cotton, James
Abstract : Introduction: Oral P2Y12 inhibitors have proven clinical efficacy in a variety of cardiological settings. The degree and time course of platelet inhibition using common P2Y12 inhibitors during the acute phase of a myocardial infarction is an under explored area. We aimed to determine the effect of clopidogrel, prasugrel and ticagrelor in the first four hours following loading in patients admitted with STEMI undergoing primary percutaneous coronary intervention (PPCI). Methods: A single centre non-randomised study in patients presenting with STEMI. All patients gave informed consent. Enrolled patients were administered a loading dose of aspirin 300mg and then either clopidogrel 600mg, prasugrel 60mg or ticagrelor 180mg prior to percutaneous coronary intervention. Platelet reactivity was measured using a Verify Now assay at 20 minutes post loading, first balloon inflation, 1 and 4 hours post loading. Results are expressed a P2Y12 reaction units (PRU). PRU ≥ 208 indicates poor antiplatelet response. The effect of the three drugs over time were assessed using 2 way ANOVA. P < 0.05 was taken as a significant result. Results: A total of 43 STEMI patients were recruited to the study. Refer to Table 1 for baseline characteristics. PRU results for the 3 drugs at 20 minutes, balloon time, 60 minutes and 240 minutes were determined. Mean dose to balloon time was 26.8 + 12.7. At balloon time, 20 minutes and 60 minutes none of the agents achieved a PRU < 208. There was a significant difference over time between clopidogrel and ticagrelor (P = 0.04), clopidogrel and prasugrel P < 0.0001 and no statistical difference was found when ticagrelor was compared with prasugrel over time (Figure 1 ). Conclusion: Clopidogrel in the context of STEMI does not provide adequate platelet inhibition as evidenced by PRU > 208 at all data collection time points, Both prasugrel and ticagrelor are superior to clopidogrel resulting in a significant reduction in the degree of platelet reactivity. Although Prasugrel and ticagrelor are comparable in terms of inhibition of platelet activity at 20 minutes, balloon inflation, 1 hour and 4 hours, they still do not achieve the desired levels of platelet inhibition necessary during PPCI as demonstrated by PRU > 208. It is possible that fast acting intravenous antiplatelet agents may have a role to play in achieving adequate platelet inhibition in the context of PPCI.